Study protocol for a feasibility randomised controlled trial of MOVE SMART—An intervention to increase physical activity, reduce sedentary behaviour and improve health outcomes in patients with psoriasis - Gladys Onambele-Pearson; Ben Ives; Ishani Khosla; Rozemarijn Witkam; Matthew Roberts; Lucy Moorhead; Emma Bedson; Russ Cowper; Girvan Burnside; Helen S. Young (PLoS ONE, 2026)
Patients with psoriasis are less physically active than age-matched controls, due to psoriasis-specific barriers; significantly limiting their ability to benefit from health-promoting levels of physical activity. We co-designed an exercise intervention, with patients, which in proof-of-concept studies, led to significantly improved psoriasis; reduced cardiovascular disease/metabolic syndrome risk and enhanced wellbeing/psychosocial functioning. This suggested increased physical activity may improve health outcomes for those with psoriasis. However, individuals remained sedentary for prolonged periods, which also has a detrimental effect on health. We therefore developed a new intervention – MOVE SMART – to increase light-intensity physical activity and interrupt sedentary behaviour. This randomised controlled clinical trial (RCT) will assess the feasibility and acceptability of MOVE SMART. Utilising a decentralised, two-arm, trial design, people with Type 1 psoriasis with/without stable psoriatic arthritis, (n = 60) will be recruited from across the UK, and randomised to intervention (MOVE SMART with “Standard Care”, n = 30) or control (“Standard Care”, n = 30). The intervention group will follow MOVE SMART for 12-weeks, followed by activities of their own choice during weeks 13–24. MOVE SMART will prompt 2-minutes of light-intensity physical activity, following 30-minutes of continuous sedentary behaviour, during daytime waking hours. The study comprises of three Workstreams. In Workstream-1 participants will use wearable devices to allow monitoring of physical behaviour and adherence to MOVE SMART. A blood pressure monitor and body weight scales will be posted to participants for use throughout the study and functional capacity will be measured by video-link. At baseline, week-12 and −24 all participants will complete self-assessment of the extent/impact of psoriasis and wellbeing. Capillary blood will be collected using home-sampling kits. In Workstream-2 acceptability of the intervention will be evaluated and the trial design will be finalised in Workstream-3. The study is registered at www.isrctn.com (ISRCTN 17400289).